Intestinal permeability changes and excretion of micro-organisms in stools of infants with diarrhoea and vomiting. Issue 4 (April 1985) - Weaver, L T; Chapman, P D; Madeley, C R; Laker, M F; Nelson, R
Abstract : The relation between diarrhoea and vomiting, the excretion of stool micro-organisms, and the passive intestinal permeability in 20 infants living in a deprived urban area was studied prospectively from birth to age 6 months. Intestinal permeability was measured from the ratio of lactulose to mannitol recovered in the urine of infants receiving feeds containing both markers. Micro-organism excretion was found to occur in both the presence and absence of gastrointestinal symptoms, but a significantly higher mean intestinal permeability was recorded in those infants with symptoms and organisms in the stool than in those with neither. An increased intestinal permeability may be a sign of mucosal damage by intestinal micro-organisms.